2010
DOI: 10.1177/0894845309357052
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Thinking and Its Relation to School Dropout

Abstract: The aim of this longitudinal research is to explore whether poorly organized occupational thinking contributes to school dropout. The 377 students in the sample were 15-16 years old when they participated in an evaluative study on career education. Kelly's method of measuring vocational constructs, the repertory grid technique, was used to measure gains in the organization of occupational thinking. Information on educational progress was gathered in a follow-up study 8 years later to examine, whether gains in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(45 reference statements)
0
4
0
1
Order By: Relevance
“…This decision in parliament is an example of how a constructive and positive development can be halted, but at the same time it is interesting to see how this occurs, through changes made during the legislative process. It can be argued that the high dropout rates from upper secondary school is in part due to this poor status of career education (Vilhjálmsdóttir, 2010). The conclusion is that this policy from 1974 has had its costs.…”
Section: Policy and Legislation On Guidance At The Compulsory School mentioning
confidence: 99%
“…This decision in parliament is an example of how a constructive and positive development can be halted, but at the same time it is interesting to see how this occurs, through changes made during the legislative process. It can be argued that the high dropout rates from upper secondary school is in part due to this poor status of career education (Vilhjálmsdóttir, 2010). The conclusion is that this policy from 1974 has had its costs.…”
Section: Policy and Legislation On Guidance At The Compulsory School mentioning
confidence: 99%
“…Results of these studies have indicated a need for career development practices at the elementary and high school levels. The results of Vilhjálmsdóttir's (2010) study also revealed that career development practices can facilitate career understanding and, in turn, reduce the likelihood of students dropping out of school. This literature, although promising, is limited and does not specifically address Latino dropout issues.…”
Section: Understanding and Preventing School Failurementioning
confidence: 99%
“…One area of counselor training that has not been addressed in the literature pertaining to Latino students' school success that logically could play a critical role in a comprehensive prevention program is career development theory. Literature about career development practices in schools is scarce; however, a few evidence-based studies have been completed (Nazli, 2007;Vilhjálmsdóttir, 2010). Results of these studies have indicated a need for career development practices at the elementary and high school levels.…”
Section: Understanding and Preventing School Failurementioning
confidence: 99%
“…La mayoría de las investigaciones realizadas en el área vocacional se han enfocado en el análisis de la estructura cognitiva (Martínez, 2005;Neimeyer, 1992b). Los índices más estudiados han sido la diferenciación e integración (Mau, 1997;Vilhjálmsdóttir, 2010). Existen pocas investigaciones realizadas con un abordaje cualitativo de los datos y, concretamente, que hayan elaborado sistemas de categorías para la evaluación del contenido temático de los constructos vocacionales (Neimeyer, 1989b), los cuales pueden ser una herramienta muy útil en el análisis de las versiones idiográficas de la RV.…”
Section: Introductionunclassified